2015
DOI: 10.24926/iip.v6i3.392
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Accessibility of Community Pharmacy Services

Abstract: There has been no funding support, no previous presentations of this work, and there are no conflicts of interest. Acknowledgement

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 6 publications
2
55
0
1
Order By: Relevance
“…It is important to note that, while pharmacists are generally considered the most accessible healthcare professional, the accessibility of pharmacy services is limited in some underserved communities [17, 19, 20]. For example, not all underserved communities have access to national drugstore retailers with established pharmacy-based immunization programs.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that, while pharmacists are generally considered the most accessible healthcare professional, the accessibility of pharmacy services is limited in some underserved communities [17, 19, 20]. For example, not all underserved communities have access to national drugstore retailers with established pharmacy-based immunization programs.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists have the advantage of being one of the most accessible healthcare professionals and are able to spend more time educating patients on their medications in comparison to other healthcare providers. 23,24 Medication therapy management (MTM) services are provided by pharmacists to help patients understand their disease state(s) and medications to optimize therapeutic outcomes. 25 These services can be provided to patients faceto-face or telephonically.…”
Section: Introductionmentioning
confidence: 99%
“…Considering their accessibility and trusted role as community health care professionals, the community pharmacist is in a unique and advantageous position to forge relationships with patients, including the systematic provision of referrals, which positively impact patients' health. Moreover, as pharmacists expand their roles in patient care and health promotion, they are becoming increasingly recognized as sources of health information; often, pharmacies serve as informal community health access points with pharmacy staff being the initial point of care for many patients . However, recent work examining medication therapy management (MTM) delivery through application of the CCM found that referrals to community health resources as part of MTM are uncommon due to pharmacist and staff reported lack of familiarity with resources available, and the perception that these referrals are not a part of MTM .…”
Section: Introductionmentioning
confidence: 99%